Design of dengue and leptospirosis prevention strategies through participatory interventions in comparison with vertical strategies in riverside areas of Alto Verde (Santa Fe Capital): Preliminary results - Avalos, Christian A.; Ricardo, Tamara; Maglianese, Mariana; Chiaraviglio, Romina; Leiva, Mariano; Bazán Rodriguez, Ludmila; Beltramo, Leda; Sanmartino, Mariana; Mendicino, Diego; Costa, Federico; Previtali, Andrea (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
This study focuses on the prevention of dengue and leptospirosis in vulnerable populations in the riverside area of the city of Santa Fe, Argentina, comparing the effectiveness of vector and reservoir control strategies through participatory interventions with a community approach, compared to traditional vertical strategies in riverside areas of Santa Fe. In the face of the hegemonic sanitary and medical model, it is necessary to provide more knowledge on the effectiveness of other possible forms of prevention, based on critical, socio-ecological, participatory models and approaches, which occur at the local scale, in the territories inhabited by the community. The methodology of the study comprised a quali-quantitative, randomized, controlled community trial with local community action. Two representative zones were selected from riverside sectors of Santa Fe, which share similar socioeconomic indices. In one area, participatory interventions were applied based on participatory action research, Citizen Science, and SEPA (Sociabilization of Evidence for Action) approaches. Simultaneously, and as a control, vertical and centralized prevention mechanisms were applied in the other zone.  In order to make comparisons of effectiveness, a characterization of the socio-environmental, sanitary, vector and reservoir conditions, and knowledge, attitudes and practices regarding these diseases was carried out in both zones, at pre- and post-intervention times.In exploratory analyses of the data collected, significant rates of change were found between both zones post-intervention, and a significant effect of the participatory interventions for response variables of health importance in dengue. Sampling for leptospirosis remains to be done